Interorgan Metabolism of Ganglioside Is Altered in Type 2 Diabetes - Irma Magaly Rivas Serna; Michelle Beveridge; Michaelann Wilke; Edmond A. Ryan; Michael Thomas Clandinin; Vera Christine Mazurak (Biomedicines, 2022)
GM3 is implicated in cell signaling, inflammation and insulin resistance. The intestinal mucosa metabolizes ganglioside and provides gangliosides for uptake by peripheral tissues. Gangliosides downregulate acute and chronic inflammatory signals. It is likely that transport of intestinal derived gangliosides to other tissues impact the same signals characteristic of inflammatory change in other chronic conditions such as Type 2 Diabetes (T2DM). The postprandial ceramide composition of GM3 and other gangliosides in plasma and chylomicrons has not been examined in T2DM. The present study assessed if diet or T2DM alters ganglioside components in plasma and chylomicrons secreted from the intestinal mucosa after a meal. GD1, GD3, and GM3 content of chylomicrons and plasma was determined by LC/triple quad MS in non-diabetic (control) and T2DM individuals in the fasting and postprandial state after 2 days of consuming a low or high fat diet in a randomized blinded crossover design. Diet fat level did not alter baseline plasma or chylomicron ganglioside levels. Four hours after the test meal, plasma monounsaturated GD3 was 75% higher, plasma saturated GD3 was 140% higher and plasma polyunsaturated GM3 30% lower in diabetic subjects compared to control subjects. At 4 h, chylomicron GD1 was 50% lower in T2DM compared to controls. The proportion of d34:1 in GD3 was more abundant and d36:1 in GD1 less abundant in T2DM compared to control subjects at 4 h. The present study indicates that T2DM alters ceramide composition of ganglioside available for uptake by peripheral tissues.